Perkembangan Akuntansi Modern melalui Pemanfaatan Kecerdasan Buatan (AI) dalam Proses Akuntansi - Harared, Bunga Anisah; Murdhaningsih, Murdhaningsih (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
The development of digital technology has brought significant changes in modern accounting practices. The integration of artificial intelligence (AI) enables the automation of accounting processes, big data analysis, and increased efficiency and accuracy in financial management. AI is applied in various aspects, including transaction recording, financial analysis, and anomaly and fraud detection. Various studies have shown that the use of AI in accounting can reduce human error, increase data processing speed, and enable more accurate strategic decision-making. This research uses a qualitative descriptive method with a literature study approach to explore the extent of AI's influence on modern accounting systems. The results show that AI supports the automation of repetitive tasks, improves the accuracy of financial reports, and reduces operational costs. However, challenges in implementing AI include data security, algorithm bias, and the need for accountants to have technology and data analysis skills. The conclusion of this study emphasizes the importance of adopting AI in accounting by considering ethical aspects, regulations, and human resource competencies. With the right strategy, AI can be a tool that supports the digital transformation of accounting without replacing the strategic role of accountants.